Optic Nerve Glioma - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The clinical presentation, diagnosis, response to therapy, and visual outcome of 18 children with optic nerve glioma are reported from the Division of Neurology, Department of Pediatrics, University of British Columbia, Vancouver, Canada.